PRODUCING 3D COMBINED MODELS BY THE SUPPORT OF IMAGE PROCESSING TECHNIQUES TO BE USED IN CITY DESIGNING APPLICATION: TAKSIM CUMHURIYET SQUARE - Sahin, Cumhur; Alkis, Ayhan (YILDIZ TECHNICAL UNIV, 2012)
Three dimensional urban modeling is used in the area of urban design most frequently. Three dimensional city square models give the impression of being inside the modeled area. For the planner, this makes it easy to read the studied area. Every kind of information related to physical space can be obtained of the model, as if you really are in the area. It helps the researcher to look at the area with the perspectives which resembles the study area. The most important component of three dimensional modeling studies is geographical data. There are emerging problems such as the quality level of existing data, its optimization, and integration. The main purpose of this study is to compare, combine and optimize the photogrammetric and terrestrial laser scanning methods in order them to be used in urban and regional planning studies. By this way, the usability, relevance of the mentioned data for the urban region planning are examined. The achieved 3D model which applied in its original scale, on 3D maps, is gained by using the real images data with the support of laser scanners. Taksim quare's combined 3D model has made great contributions to city planner's micro scale city applications.
Keywords: 3D city model; terrestrial laser scanner; terrestrial photogrammetry; Engineering